Evaluating the effects of triclosan on 3 field crops grown in 4 formulations of biosolids. (13th February 2017) - Shahmohamadloo, René S.; Lissemore, Linda; Prosser, Ryan S.; Sibley, Paul K.
Abstract: A growing body of evidence suggests that amending soil with biosolids can be an integral component of sustainable agriculture. Despite strong evidence supporting its beneficial use in agriculture, there are concerns that chemicals, such as pharmaceuticals and personal care products, could present a risk to terrestrial ecosystems and human health. Triclosan is one of the most commonly detected compounds in biosolids. To date, laboratory studies indicate that triclosan likely poses a de minimis risk to field crops; however, these studies were either conducted under unrealistic exposure conditions or only assessed 1 or 2 formulations of biosolids. The purpose of the present study was to characterize the effects of triclosan on field crops in soils amended with 4 different formulations of biosolids (liquid, dewatered, compost, and alkaline‐hydrolyzed), containing both background and spiked triclosan concentrations, following best management practices used in the province of Ontario. Three crop species (corn, soybean, and spring wheat) were evaluated using several plant growth endpoints (e.g., root wet mass, shoot length, shoot wet/dry mass) in 70‐d to 90‐d potted soil tests. The results indicated no adverse impact of triclosan on any crop‐biosolids combination. Conversely, amending soil with biosolids either enhanced or had no negative effect, on the growth of plants. Results of the present study suggest little risk of triclosan to crops in agricultural fields amended with biosolids. Environ Toxicol Chem 2017;36:1896–1908. © 2016 SETAC